Interferon‐α promotes MHC I antigen presentation of islet β cells through STAT1‐IRF7 pathway in type 1 diabetes. Issue 2 (24th March 2022) - Jiang, Hemin; Li, Yue; Shen, Min; Liang, Yucheng; Qian, Yu; Dai, Hao; Xu, Kuanfeng; Xu, Xinyu; Lv, Hui; Zhang, Jie; Yang, Tao; Fu, Qi
Abstract: Type 1 diabetes (T1D) is a T cell‐mediated autoimmune disease. Increased incidence of T1D was reported in patients receiving IFN‐α treatment. However, the exact mechanisms of IFN‐α that facilitate the pathogenesis of T1D are not fully understood. To explore the mechanism of IFN‐α on the immune system and islets, non‐obese diabetic (NOD) mice were injected with IFN‐α and the progression of autoimmune insulitis was assessed by haematoxylin and eosin (HE) staining, immunohistochemical and flow cytometry analysis. Transcriptional profiling of islets treated with IFN‐α was explored by RNA‐seq. IFN‐α induced antigen presentation was evaluated by qRT‐PCR, western blot and immunofluorescence, and key transcription factors were inhibited by small interfering RNAs (siRNAs). Our data show that IFN‐α contributed to the progression of autoimmune insulitis in NOD mice by promoting the proliferation of CD8+ T cells. IFN‐α upregulated antigen presentation related genes MHC I, TAP1, B2M, PSMB8, NLRC5 and transcriptional regulator STAT1, STAT2, IRF7 at a time and dose‐dependent manner. The silence of STAT1 or STAT2 both weakened IFN‐α‐induced increase of antigen presenting related molecules. IRF7 was also merely influenced by STAT1 silence. The knockdown of IRF7 decreased the IFN‐α induced expressions of TAP1, PSMB8 and MHC I and prevented the expression of STAT2 but not STAT1. Our study demonstrated that STAT1‐IRF7‐MHC I complex axis were crucial for IFN‐α signalling in islets, and created positive feedback through IRF7‐STAT2 cascade amplifying signals which accelerated the process of T1D. Abstract : In β cells, IFN‐α binds to the IFNRs and leads to the nuclear translocation of STAT1 and IRF7, which in turn activates the STAT1‐IRF7 axis to increase the expression of antigen presenting molecules (TAP1, PSMB8 and MHC I). These actions create positive feedback through IRF7‐STAT2 cascade amplifying signals and promote the proliferation of CD8+ T cells and insulitis.